Effects of smoking cessation on plasma clozapine concentrations in male patients with schizophrenia during the COVID-19 pandemic - Botao Ma; Hongzhen Fan; Siyuan Qi; Fude Yang; Huimei An (Frontiers in Psychiatry, 2023)
IntroductionThis study aimed to investigate the effect of smoking cessation on plasma clozapine (CLO) concentrations in long-term hospitalized Chinese male patients with schizophrenia treated with CLO during the COVID-19 pandemic.MethodsTherapeutic drug monitoring (TDM) data for CLO were collected at Beijing HuiLongGuan Hospital between December 1, 2019 (before smoking cessation) and January 31, 2020 (after smoking cessation) in this retrospective study. Fifty-three male smokers and inpatients with schizophrenia who were treated with CLO were included. Plasma concentrations of CLO were measured using high-performance liquid chromatography–tandem mass spectrometry. The fagerstrom test for nicotine dependence (FTND) was used to assess smoking behavior.ResultsThe plasma CLO concentrations and dose-corrected plasma CLO concentrations were significantly increased by 29.3 and 23.5%, respectively, after smoking cessation.DiscussionThe results suggested that clinicians and pharmacists should adjust the CLO dose based on changes in smoking status in patients stabilized with CLO during the COVID-19 pandemic. Careful TDM for CLO should be performed prior to dose adjustment，to reduce the increased risk of smoking cessation induced side effects, especially for older patients receiving multiple medications.